Food Security Resilience and Humanitarian Aid in Mali: A Case Study of Bandiagara Cercle - Innocent Mumararungu; Gisaro Ca-Madeberi Ya-Bititi; John Rwirahira; Philippe Burny (International Journal of Food Science)
Mali’s food security strategies focus on improving agriculture, water management, and diversifying livelihoods. While initiatives like climate-smart agriculture show promise, challenges like limited resources, market access, and political instability persist. Gender inequalities and reliance on external aid further hinder progress, making it difficult for Mali to build sustainable, self-reliant food systems and ensure long-term resilience. This research assessed the effectiveness of humanitarian aid interventions in enhancing food security resilience in the Bandiagara Region of Mali. It is aimed at evaluating the quality and sufficiency of the food provided to beneficiaries, as well as the alignment of aid efforts with local needs. The study employed a mixed-methods approach, combining quantitative household surveys with 295 respondents across 14 villages and qualitative data through semistructured interviews with 37 local authorities selected on purposive sampling and focus group discussions with beneficiaries. The findings indicated that while the aid interventions were generally relevant and well executed, with beneficiaries expressing satisfaction with the quality of the millet provided, there were significant concerns regarding the quantity of food distributed. Many beneficiaries felt that the portions were insufficient to meet their needs, especially in the context of recurring food shortages. This highlighted the need for more tailored, context-specific aid allocation strategies, ensuring that the quantity of food provided aligns better with local requirements and the scale of food insecurity, thereby enhancing the overall effectiveness of humanitarian support. It is recommended to expand and continue millet distribution programs, with enhanced monitoring mechanisms to ensure resource effectiveness. Emphasizing customized food allocation and increased community engagement will strengthen local ownership and resilience. By aligning aid with local needs and improving intervention targeting, these strategies are aimed at creating a more sustainable and equitable food security system in the Bandiagara Region, better equipping it to withstand future food insecurity challenges.